Genetic Diversity and Antibiotic Resistance Patterns of Staphylococcus Aureus Isolated from Leaf Vegetables in Korea. Issue 7 (27th May 2015) - Hong, Jisoo; Kim, Yangkyun; Kim, Jonguk; Heu, Sunggi; Kim, Se‐ri; Kim, Kwang‐Pyo; Roh, Eunjung
Abstract Staphylococcus aureus is an important foodborne pathogen on global basis. The current study investigated the genetic patterns in S. aureus isolates from leaf vegetables (n = 53). Additional isolates from livestock (n = 31) and humans (n = 27) were compared with the leaf vegetable isolates. Genes associated with toxins, antibiotic resistance, and pulsed‐field gel electrophoresis (PFGE) patterns were analyzed. At least 1 enterotoxin‐encoding gene (sea, seb, sec, sed, and see) was detected in 11 of 53 (20.75%) leaf vegetable isolates. When the agr (accessory gene regulator) grouping was analyzed, agr II was the major group, whereas agr IV was not present in leaf vegetable isolates. All S. aureus isolates from leaf vegetables were resistant to more than one of the antibiotics tested. Nineteen of 53 (35.85%) isolates from leaf vegetables exhibited multidrug‐resistance, and 11 of these were MRSA (methicillin‐resistant S. aureus). A dendrogram displaying the composite types of S. aureus isolates from 3 origins was generated based on the combination of the toxin genes, agr genes, antibiotic resistance, and PFGE patterns. The isolates could be clustered into 8 major composite types. The genetic patterns of S. aureus isolates from leaf vegetables and humans were similar, whereas those from livestock had unique patterns. This suggests some S. aureus isolates from leaf vegetables to be of human origin.